(3OQGSI abgjI ebGQfI Hjf MbjbI GdeQGHMI HUhQJjgG GdeQcHI hGdHSjWI hGdeeGQSGJ GdfXQjI hGdYdejI dHjY GdeQGHMI ddBeQ HGdTQGA aj GdeUGQa GdGSdGejIs - (3CMeO SGde(B, (3edMes ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2005)
(3WQjbI GdeQGHMI aj GdHjY hJbSjegG Gdi HSjWI heQcHI(B:(3TQhW GdeQGHMI,eG jLH HjGfg aj GdeQGHMI GdHSjWI,eGjLH HjGfg eGjdMb HQCS GdeGd(B-(3GdeQGHMI GdeQcHI,MbjbI GdeQGHMI GdeQcHI,ebGQfI Hjf GdeQGHMI GdHSjWI hGdeQcHI,GdeQGHMI GdNGQLjI,eTQhYjI GdeQGHMI GdeQcHI(B.s
(3HjHdjhZQGajG U(B.289s
Keywords: (3GdHfhc GdGSdGejIs